Impact of the Interruption Duration on Photoluminescence Properties of MOCVD-Grown GaAsP/InAlGaAs Quantum Well Structures - Bin Wang; Yugang Zeng; Xuezhe Yu; Weijie Gao; Wei Chen; Haoyu Shen; Li Qin; Yongqiang Ning; Lijun Wang (Nanomaterials)
The growth interruption technology is introduced to the growth of GaAsP/InAlGaAs quantum well (QW) structure using metal–organic chemical vapor deposition (MOCVD). The effect of growth interruption time (GIT) on the crystalline quality and optical properties are investigated. The two distinctive emission peaks are the transition recombination between the electron level of conduction band and the light and heavy hole level of valence band in the photoluminescence (PL) at room temperature. The PL peaks present a redshift and merge together with the increasing GIT, which is attributed to the QW energy level shift caused by the increase in arsenic concentrations in GaAsP QW, the diversified thickness of QW and the variations of indium components in the InAlGaAs barrier layer. The Gaussian deconvolution parameters in temperature-dependent PL (TDPL) show that the GaAsP/InAlGaAs QW with a GIT of 6 s has a 565.74 meV activation energy, enhancing the carrier confinement in QW and the PL intensity, while the 6 s-GIT GaAsP QW has the increasing interface roughness and the non-radiative centers at the InGaAsP intermediate layer, leading to a spectral broadening. The QW with 10 s-GIT exhibits a small full width at half maximum (FWHM) with the various temperature, indicating reduced interface roughness and excellent crystal quality. An increase in GIT may be suitable for optimizing the optical properties of GaAsP/InAlGaAs QW.